PH, Nanosheet Concentration, and Antioxidant Affect the Oxidation of Ti3C2Tx and Ti2CTx MXene Dispersions. Issue 20 (26th August 2020) - Zhao, Xiaofei; Vashisth, Aniruddh; Blivin, Jackson W.; Tan, Zeyi; Holta, Dustin E.; Kotasthane, Vrushali; Shah, Smit A.; Habib, Touseef; Liu, Shuhao; Lutkenhaus, Jodie L.; Radovic, Miladin; Green, Micah J.
Abstract: The chemical stability of 2D MXene nanosheets in aqueous dispersions must be maintained to foster their widespread application. MXene nanosheets react with water, which results in the degradation of their 2D structure into oxides and carbon residues. The latter detrimentally restricts the shelf life of MXene dispersions and devices. However, the mechanism of MXene degradation in aqueous environment has yet to be fully understood. In this work, the oxidation kinetics is investigated of Ti3 C2 T x and Ti2 CT x in aqueous media as a function of initial pH values, ionic strengths, and nanosheet concentrations. The pH value of the dispersion is found to change with time as a result of MXene oxidation. Specifically, MXene oxidation is accelerated in basic media by their reaction with hydroxyl anions. It is also demonstrated that oxidation kinetics are strongly dependent on nanosheet dispersion concentration, in which oxidation is accelerated for lower MXene concentrations. Ionic strength does not strongly affect MXene oxidation. The authors also report that citric acid acts as an effective antioxidant and mitigates the oxidation of both Ti3 C2 T x and Ti2 CT x MXenes. Reactive molecular dynamic simulations suggest that citric acid associates with the nanosheet edge to hinder the initiation of oxidation. Abstract : Oxidation kinetics of Ti3 C2 T x and Ti2 CT x MXene nanosheets in aqueous media are accelerated at high pH and at low MXene concentrations. However, this degradation process can be mitigated; citric acid acts as an effective MXene antioxidant for both Ti3 C2 T x and Ti2 CT x .